Particle Swarm Optimized Voltage Stability Analysis Of IEEE 14 Bus System with SVC and TCSC - Pradip, Rahul; Kotwal, Chetan D; Pujara, Shital M (International Journal of Computer Sciences and Engineering, 2019)
Over a last few decade’s voltage instability is a concern phenomenon in power industry. The main cause of voltage instability is the deficit of reactive power in the system and the Active Power losses due to increased inductive reactance of transmission line. Flexible AC transmission system (FACTS) devices can improve the line losses by varying inductive reactance there by increasing Active Power in the system and controlling reactive power by Facts devices which tends to control voltage within the specific limit. In this paper the work is proposed with the help of IEEE 14 bus system in Power World Simulator and comparison have been made in MATLAB. The index of voltage stability Fast Voltage Stability Index (FVSI) gives information about the line which is prone to voltage collapse. At last the location and rating of SVC and TCSC are optimized with help of Particle Swarm Optimization Algorithm to get the voltage within a specific range at all the load buses.